Museu em Movimento: O Museu Capixaba do Negro “Verônica da Pas” (Mucane) - Ativismo, Acervo e Atividades - Afonso, Bruna Gomes (2022)
The present work is associated with historical-artistic and cultural material and immaterial studies on blacks in Brazil, especially in the regional context of Vitória, in Espírito Santo. The research was developed from a survey of the exhibitions and activities carried out at the Museu Capixaba do Negro “Verônica da Pas” (Mucane), from the reopening of 2012, as well as the constitution of its collection throughout its trajectory. The museum was founded in 1993 and is located in Vitória (ES). With this approach, the research aimed to analyze the formation and current situation of the museum, through interviews, conversations and field research, as well as analysis of primary and secondary sources. The results presented constitute an effort to organize the data on Mucane, also understanding them in a configuration of museums in the country.